Complicaciones materno perinatales en parto post cesárea previa en pacientes ingresadas en el Hospital General Martín Icaza en el periodo de mayo 2022- abril 2023. - Gaspar Bone, Kerly Dellaneira (2023)
Cesarean section is a surgical intervention that consists in the removal of the fetus through an incision in the uterus. The problem lies in the fact that many of these cesarean sections may not have a clear indication, with an increase in maternal complications and avoidable perinatal morbidity. The present research work is focused on women who have been admitted to the Hospital General Martín Icaza with a diagnosis of term pregnancy plus previous uterine scar in the period May 2022 - April 2023, with the objective of describing and knowing the complications that may occur in a post cesarean delivery, both maternal and perinatal. The methodology used for this research work was a historical-logical method, in addition to being non-experimental, documentary, descriptive, longitudinal (retrospective). The population corresponds to the total number of patients attended in the obstetric emergency area of the Hospital General Martín Icaza, being a total of n= 1047 patients and the sample taken into account was 221 patients who were admitted with pregnancies at term plus previous uterine scar. The results obtained in the research show that of the 100% of the patients admitted, 4% presented maternal complications and 2% presented perinatal complications. In conclusion, it was found that a vaginal delivery after a successful cesarean section has fewer complications than a repeat cesarean section.